(untitled) (International Journal of Applied Research in Management and Economics, 2018)
Introduction: with the emergence of e-commerce and new economic conditions, developing stronger communications with customers has become more important. The aim of this study was to provide a model of the relationship between software, hardware, and organizational factors in the success of implementing a comprehensive customer relationship management (CRM) system using a fuzzy mapping function (FCM). This study was a case study in the international transportation of Iranian forwarders. Method: the method of this study was descriptive and a questionnaire was used as a measuring tool. The population of this research was included CEO, managers, and experts of various departments of international shipping and shipping companies, customers of international shipping companies and shipping companies, managers and ICT experts who have at least a bachelor’s degree and upper and have five years of work experience in this area. 110 participated in this study. In this research, the FCM fuzzy mapping technique was used to investigate and calculate the impact of factors on the achievement and success of implementing a comprehensive customer relationship management system in international shipping companies. This was the first method used in the international shipping and shipping industry. Findings: Based on the results of this study, it can be said that among the predictive variables, the variable of human resources and education of individuals, could predict with the confidence level of 0.99, and 0.53 of the criterion variable, and the software variable, with the confidence level of 0.95, and 0.38 of criterion variable and using FCM fuzzy mapping technique, it was observed that among four factors affecting the success of the implementation of the customer relationship management system in international shipping and shipping companies, various factors affect each other with different coefficients. Finally, the factor of human resources and training of people with a coefficient of 0.89 had the most impact on customer relationship management.